Matrix stiffness-induced myofibroblast differentiation is mediated by intrinsic mechanotransduction. - Huang, X; Yang, N; Fiore, V; Barker, T; Sun, Y; Morris, S; Ding, Q; Thannickal, V; Zhou, Y (2012)
The mechanical properties of the extracellular matrix have recently been shown to promote myofibroblast differentiation and lung fibrosis. Mechanisms by which matrix stiffness regulates myofibroblast differentiation are not fully understood. The goal of this study was to determine the intrinsic mechanisms of mechanotransduction in the regulation of matrix stiffness-induced myofibroblast differentiation. A well established polyacrylamide gel system with tunable substrate stiffness was used in this study. Megakaryoblastic leukemia factor-1 (MKL1) nuclear translocation was imaged by confocal immunofluorescent microscopy. The binding of MKL1 to the α-smooth muscle actin (α-SMA) gene promoter was quantified by quantitative chromatin immunoprecipitation assay. Normal human lung fibroblasts responded to matrix stiffening with changes in actin dynamics that favor filamentous actin polymerization. Actin polymerization resulted in nuclear translocation of MKL1, a serum response factor coactivator that plays a central role in regulating the expression of fibrotic genes, including α-SMA, a marker for myofibroblast differentiation. Mouse lung fibroblasts deficient in Mkl1 did not respond to matrix stiffening with increased α-SMA expression, whereas ectopic expression of human MKL1 cDNA restored the ability of Mkl1 null lung fibroblasts to express α-SMA. Furthermore, matrix stiffening promoted production and activation of the small GTPase RhoA, increased Rho kinase (ROCK) activity, and enhanced fibroblast contractility. Inhibition of RhoA/ROCK abrogated stiff matrix-induced actin cytoskeletal reorganization, MKL1 nuclear translocation, and myofibroblast differentiation. This study indicates that actin cytoskeletal remodeling-mediated activation of MKL1 transduces mechanical stimuli from the extracellular matrix to a fibrogenic program that promotes myofibroblast differentiation, suggesting an intrinsic mechanotransduction mechanism.